Design and study of a pneumatically actuated inverted pendulum system controlled using a programmable logic controller. (August 2020) - Pontin, Marco; Colombo, Federico; Mazza, Luigi; Raparelli, Terenziano
This article investigates an inverted pendulum on a mobile cart (mobile inverted pendulum) controlled via a programmable logic controller and actuated by a double-acting pneumatic cylinder. The study is conducted both theoretically, by modeling and simulating the entire system, and experimentally, using a specially developed test bench. Four low-cost 2/2 proportional valves are used for cylinder control. The control architecture consists of two nested control loops with proportional–integral–derivative compensators. To reduce cost, a programmable logic controller was used to manage both the system control and data acquisition. The results of the simulations carried out using linear and nonlinear models of the system were validated by comparison with those obtained experimentally.